Diversity for sustaining livelihoods: examples, constraints and lessons learnt - Taylor, M.; Jaenicke, H.; Hunter, D.; McGregor, A.; Lyons, G. (International Society for Horticultural Science, 2015)
Strengthening and expanding options people have to sustain livelihoods under a changing climate is a key element in enhancing adaptive capacity and resilience. Many traditional food crops and farming systems have demonstrated their relative resilience to extreme climate events such as cyclones, flooding and saltwater inundation; promoting these crops, and ensuring diverse farming systems, is essential to strengthening livelihoods, food and nutritional security, and agroecosystem resilience in an uncertain future. Diversification opens up opportunities for innovation in production methods that build on or modify traditional cropping systems. It also contributes to diversifying diets and improving nutrition outcomes. Diversification supports processing and value adding, strengthening the food security function of the crop but also providing income generating opportunities. Increasing efforts to support commercialization of indigenous species, often with an inherent resilience to climate variability can be a viable option for economic diversification. In a rapidly changing future, access to novel germplasm through planting material networks, information, and technical support will be essential. Further, empowering communities to use these services to adopt and adapt climate-resilient strategies through participatory and community-based approaches will be critical, as will relevant supportive policies and institutions. Enhancing human and social capital and diversifying livelihood options are vital components of any strategy which aims to assist communities to manage the impact of climate change. This paper discusses how this approach is being implemented in several countries, the constraints faced and the lessons learnt.